Improvement of Laboratory Capacity in SMK Manangga Pratama Tasikmalaya - Rizki Muliawan; Markus Markus; A S Margana; Cecep Sunardi; Nur Khakim; E Erham (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
SMK Manangga Pratama consists of several majors including Motorcycle Business Engineering (TBSM), Automotive Light Vehicle Engineering (TKRO), and Sofware Engineering (RPL). In major Automotive Light Vehicle Engineering (TKRO), some subjects discuss the Air Conditioning system (automotive AC and split room AC). The problem is the lack of equipment for vacuuming, and charging refrigerants for automotive AC units to be used and empowered as a learning resource. The main cause is the lack of affordable equipment for service, unit maintenance. This of course will be a problem when the students have graduated and need direct application to the Automotive AC system and the room. There are about 110 students from the Automotive Light Vehicle Engineering (TKRO) Department in each batch, with such a large number, it would be better if they were given an additional briefing on these skills. This PkM program has been equipped and provided with equipment and service equipment to be used by students as a training unit in improving their skills. The manufacture of tables and assembly of training units for automotive AC service completeness (charging, pumping, and other tools) will be carried out on the Polban Bandung campus. Instructor trainers in this PkM training program are several teaching staff in the Refrigeration and Air Conditioning Engineering Department, while the unit is a complete unit for automotive air conditioning units and rooms, namely (charging, pumping, and other tools). The implementation of community service activities majoring in refrigeration and air conditioning engineering POLBAN as a form of higher education tri dharma has been completed on October 28-29 at SMK Manangga Pratama. The activity consisted of making practicum tools for strengthening school laboratories, accompanied by providing training for the service and maintenance of air conditioning machines (AC).